MicroRNA Changes in Cerebrospinal Fluid After Subarachnoid Hemorrhage. Issue 9 (September 2017) - Bache, Søren; Rasmussen, Rune; Rossing, Maria; Laigaard, Finn Pedersen; Nielsen, Finn Cilius; Møller, Kirsten
Abstract : Background and Purpose—: Delayed cerebral ischemia (DCI) accounts for a major part of the morbidity and mortality after aneurysmal subarachnoid hemorrhage (SAH). MicroRNAs (miRNAs) are pathophysiologically involved in acute cerebral ischemia. This study compared miRNA profiles in cerebrospinal fluid from neurologically healthy patients, as well as SAH patients with and without subsequent development of DCI. Methods—: In a prospective case–control study of SAH patients treated with external ventricular drainage and neurologically healthy patients, miRNA profiles in cerebrospinal fluid were screened and validated using 2 different high-throughput real-time quantification polymerase chain reaction techniques. The occurrence of DCI was documented in patient charts and subsequently reviewed independently by 2 physicians. Results—: MiRNA profiles from 27 SAH patients and 10 neurologically healthy patients passed quality control. In the validation, 66 miRNAs showed a relative increase in cerebrospinal fluid from SAH patients compared with neurologically healthy patients ( P <0.001); 2 (miR-21 and miR-221) showed a relative increase in SAH patients with DCI compared with those without ( P <0.05) in both the screening and validation. Conclusions—: SAH is associated with marked changes in the cerebrospinal fluid miRNA profile. These changes could be associated to the development of DCI. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01791257. Abstract : Supplemental Digital Content is available in the text.